2015
DOI: 10.7553/80-2-1527
|View full text |Cite
|
Sign up to set email alerts
|

The use of electronic information resources for academic research by postgraduate students at Delta State University, Abraka, Nigeria

Abstract: This study used a structured questionnaire to investigate the usage of Electronic Information Resources (EIR) for academic research by 150 postgraduate students at Delta State University, Abraka, Nigeria. Interviews with some students and selected individuals at the institution were also conducted. The study looked into whether postgraduate students had access to EIR; whether they knew how to use computers in order to have access to EIR; the extent to which they knew and were aware of EIR; the current status o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The study recommends the introduction of information competency across the curriculum and the introduction of a one-unit course to be taught at all levels. Okite-Amughoro et al (2014) studied the use of ERs for academic research by postgraduate students and revealed that they are aware of the existence of ERs, but the optimal use of them is hampered by limited access due to a lack of information-searching skills, limited space, slow bandwidth and erratic power supply.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study recommends the introduction of information competency across the curriculum and the introduction of a one-unit course to be taught at all levels. Okite-Amughoro et al (2014) studied the use of ERs for academic research by postgraduate students and revealed that they are aware of the existence of ERs, but the optimal use of them is hampered by limited access due to a lack of information-searching skills, limited space, slow bandwidth and erratic power supply.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another observation is that though the literature is rife with the use of ERs in libraries, the focus has mostly been on the use of these resources by academics and postgraduate students. The research method adopted in most of the studies have been quantitative (Dolo-Ndlwana, 2013; Ingutia-Oyieke and Dick, 2010; Okite-Amughoro et al , 2014; Shuling, 2006). This article adopts a qualitative approach to investigate the use of ERs by undergraduate students in a historically disadvantaged university in South Africa to suggest ways in which the use of these resources may be enhanced at this and other universities in South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, postgraduate students are required to undergo specialized training in the form of course works, practicals, and research in their areas of interests for the award of higher degrees. In the distant past, postgraduate research in tertiary institutions was dominated by the use of printed materials as primary sources of information (Okite-Amughoro, Makgahlela, & Bopape, 2014). This required the students to be physically present either in the libraries or the classrooms to access information and learn.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, these technologies are used to improve subscription and access to electronic journals. Basically, libraries use a substantial amount of their annual budgets on subscriptions to electronic resources which provide many advantages over conventional print journals [2][3]. Findings from a study done in USA, Canada, Brazil, Argentina, Chile, Mexico, Columbia, Peru, Venezuela, Uruguay, Europe, Asia, Saudi Arabia, Turkey and Israel show that 71% of their academic institutions subscribe to ejournals.…”
Section: Introductionmentioning
confidence: 99%